Nano-based approaches for the treatment of neuro-immunological disorders: a special emphasis on multiple sclerosis - Archna Panghal; S. J. S. Flora (Discover Nano)
Abstract Multiple sclerosis (MS) is a neuroimmunological disorder which causes axonal damage, demyelination and paralysis. Although numerous therapeutics have been developed for the effective treatment of MS and a few have been approved in recent decades, complete remission and treatment of MS remain a matter of concern. Nanotechnology is a potential approach for manipulating the properties of materials at the molecular level to attain desired properties. This approach is effective in the treatment of several CNS disorders by enhancing drug delivery, bioavailability and efficacy. We have briefly discussed the neuroimmunological disorders with a particular emphasis on MS. We also explored nanoengineered drug delivery systems, describing several nano-formulations for the treatment of MS, challenges and future of nanotechnology.